Influence of modification methods on physicochemical and structural properties of soluble dietary fiber from corn bran - Sheng Li; Nannan Hu; Jinying Zhu; Mingzhu Zheng; Huimin Liu; Jingsheng Liu (Food Chemistry: X, 2022)
Soluble dietary fiber (SDF), which is a component of dietary fibers exhibit many physiological functions, biological activity, and good gel forming ability. In this study, extraction of SDF from corn bran was evaluated using twin-screw extrusion and ultrasonic treatment and the combinations of the respective methods with dual enzyme hydrolysis. The monosaccharide compositions, molecular weight, physicochemical properties, and structural and functional characteristics were determined. The results showed that ultrasonic and twin-extrusion treatments significantly increased the SDF content from 2.42 to 4.58 and 6.54%, respectively. Dual enzyme hydrolysis further increased the SDF content. Modification treatment changed the monosaccharide composition, improved physicochemical and functional properties, such as water and oil holding capacity, nitrite adsorption, and antioxidative ability. In conclusion, physical modification combined with enzyme treatment distinctly improved the extraction yield, physicochemical and functional properties of SDF. Therefore, the modified SDF is suitable as a functional food additive.